Human Resource Competency Development in Facing the Challenges and Opportunities of the Industry 4.0 Era - Aji, Bagas Ananta; Ikhlas, Disa Insanul; Wati, Intan Ratna (Research Horizon, 2024)
In an era of technological advancements such as automation, artificial intelligence (AI), and the Fourth Industrial Revolution, the global labor market faces significant challenges, requiring the workforce to continuously adapt to new skills. Increasing global competition has heightened the demand for relevant hard and soft skills, enabling workers to contribute effectively within organizations. This study aims to analyze the role of education and training in supporting high-performing employees in the era of globalization and digitalization. Education and training are viewed as key instruments in fostering a competitive workforce, aligned with the ever-evolving demands of industry. The study employs a literature review method, referencing various studies. The findings indicate that structured, adaptive education and training are essential in shaping a superior and competitive workforce, capable of swiftly adapting to technological changes and market demands. This research enriches the literature on the importance of education and training in addressing skill gaps and supporting superior workforce performance in the era of globalization and technology. It also encourages companies to strategically and sustainably adopt technology-based training to enhance workforce skills.